Analisis Pemasaran Digital Usaha Mikro Kecil Menengah pada Teh Rosella di Kelurahan Ngipik - Falhamdany, Zhusuf; Kusumasari, Indah Respati (Jurnal Bisnis Indonesia, 2024)
The development of technology nowadays has allowed Small and Medium Enterprises (SMEs) to growrapidly through social media. This is because business owners can utilize technology well. However,there are still business owners in Kelurahan Ngipik who have not utilized this technology called socialmedia. Therefore, we are helping business owners in Kelurahan Ngipik to create online marketingthrough social media and applications such as ShopeeFood, etc. Digital marketing for Rosella Tea,which is still in the marketing stage via social media Instagram, is expected to increase sales ofRosella Tea products.Keywords: Sale; Marketing; Digital; Ngipik; Media